(untitled) (Medico Legal Update, 2021)
Background: Nasopharyngeal carcinoma (NPC) ranks first for head and neck malignancies, and radiotherapy is a recommended treatment. Most post-radiotherapy NPC patients experience oropharyngeal dysphagia that results in pharyngeal residue. Pharyngeal residue is thought to be a risk factor for aspiration-penetration. Objective: Examining the correlation between pharyngeal residue and penetration-aspiration in postradiotherapy NPC patients. Method: Participants have been identified since 2018 to find out the total number of NPC patients. In the period January-October 2019, identification of NPC patients was performed according to participant criteria. Participants were examined for fiberoptic endoscopic evaluation of swallowing (FEES), pharyngeal residue using the Yale Pharyngeal Residue Severity Rating Scale (YPR-SRS), and penetration-aspiration using Penetration-Aspiration Scale (PAS). Statistical tests were used Spearman correlation test with p<0.05. Results: The highest participant’s pharyngeal residue appeared in vallecula when given soft bolus (96.55%), and in pyriform sinus when given thick liquid bolus (72.41%). Most participants with soft bolus had the highest negative penetration (72.59%) and positive penetration in thick liquid bolus (51.72%), while most had negative aspirations with the lowest value (89.66%). There is aspiration in 10.34% of patients when given a dilute liquid. There was a significant correlation between pharyngeal residue in vallecula and pyriform sinus with penetration-aspiration (p<0.05). There was a positive association with the use of soft bolus (r=0.623), thick liquid bolus (r=0.631), and dilute liquid bolus (r=0.891). Conclusions: There is a significant association between pharyngeal residue and penetration-aspiration in post-radiotherapy NPC patients.